LabSAR, a one-GCP coregistration tool for SAR–InSAR local analysis in high-mountain regions - Weissgerber, Flora; Charrier, Laurane; Thomas, Cyril; Nicolas, Jean-Marie; Trouvé, Emmanuel (Frontiers in Remote Sensing, 2022)
The coregistration of single look complex (SLC) SAR images for InSAR or offset tracking applications is often performed by using an accurate DEM and precise orbital information. However, in cold regions, such DEMs are rare over high latitudes areas or not up-to-date over fast melting glaciers for instance. To overcome this difficulty, we propose in this paper a coregistration method preserving InSAR phase information that only requires a 3D point of reference instead of a full DEM. Developed in a Python toolbox called LabSAR, the proposed method only uses orbital information to coregister the images on the sphere centered on the Earth center passing by the ground control point (GCP). Thanks to the use of the orbital information, the so-called orbital fringes are compensated without having to estimate them. This coregistration method is compared to other approaches in two different types of applications, InSAR and offset tracking, on a PAZ Dual-Pol Temporal Stack covering the Mont Blanc massif (Western European Alps). First, InSAR measurements from LabSAR are compared with the results of the Sentinel-1 ESA Toolbox (SNAP). The LabSAR interferograms exhibits clearer topographical fringes, with fewer parameters to set. Second, offset tracking based on LabSAR coregistated images is used to measure the displacement of the Bossons glacier. The results are compared with those obtained by a conventional approach developed in the EFIDIR tools. By evaluating the uncertainties of both approaches using displacements over stable areas and the temporal closure error, similar uncertainty values are found. However, velocity values differ between the two approaches especially in areas where the altitudes are different from the altitude of the reference point. The difference can reach up to 0.06 m/day, which is in the range of the glacier velocity measurement uncertainty given in the literature. The impact of the altitude of the reference point is limited: this single GCP can be chosen at the median altitude of the study area. The error margin on the knowledge of this altitude is 1000 m, which is sufficient for the altitude to be considered as known for a wide range of study areas in the world.